Aquaculture Methods for a Genetically Managed Population of Endangered Delta Smelt. (21st February 2013) - Lindberg, Joan C.; Tigan, Galen; Ellison, Luke; Rettinghouse, Theresa; Nagel, Meredith M.; Fisch, Kathleen M.
Abstract: In response to Federal listing of the Delta Smelt Hypomesus transpacificus as a threatened species in 1993, intensive fish culture techniques were developed to provide a supply of fish for research activities. The Delta Smelt was listed as endangered by the state of California in 2009, and several agencies worked quickly to develop a captive refuge population under genetic management. Captive 2‐year‐old wild‐origin Delta Smelt served as the founding population in 2008. Each year, 250 genetically selected, single pair crosses are made in vitro, and the resultant full‐sibling families are combined to rear in multifamily groups. Typically, eight families are reared together from egg to adult stage, with 80% or more of the initial families represented at the adult stage. Multifamily rearing provides an efficient way of achieving a breeding population of 500 in a smaller facility. Juvenile survival increased from 18% in 2009 to 39% in 2010, as facilities and methodologies improved. Growth rate also increased significantly from 2009 to 2010 (from 0.19 to 0.25 mm/d). Subdermal alphanumeric tags identified individuals and allowed spawning of select individuals to preserve genetic diversity in the refuge population. Group marking, by adipose fin clip, provided efficiencies in time and space. Tagging and genetic analyses enabled in vitro spawning of recommended pair crosses each year. At present, we recommend completing the majority of spawning from February to mid‐May and continuing to augment the refuge population with wild fish each year. The refuge population provides one type of safeguard against species extinction and provides an example for endangered fish culture.